Is there poverty convergence? - Jesús Crespo Cuaresma; Stephan Klasen; Konstantin M. Wacker (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Martin Ravallion ("Why Don't We See Poverty Convergence?" American Economic Review, 102(1): 504-23; 2012) presents evidence against the existence of proportionate convergence in global poverty rates despite convergence in household mean income levels and the link between income growth and poverty reduction. We show that heterogeneity in this link affects the evidence of poverty convergence and that this result depends on the sample selected, especially on the inclusion of transition economies with poorly measured low poverty incidences. Motivating the poverty convergence equation with an arguably superior semi-elasticity specification, we find robust evidence of convergence in absolute poverty rates.
Keywords: I32; D31; P36; 330; poverty convergence; income inequality; economic growth; poverty trap; transition economies